Implementation of Role Play in Financial Literacy in Fiqih Learning for Buying and Selling - Muhammad Habibul Arsy; Ahmad Ma’ruf; M Jamhuri; Ali Mohtarom (Universitas Nurul Jadid, 2026)
This research aims to analyze the implementation of the role-play method in Fiqh learning, specifically regarding buying and selling (buy and sell) materials, and its influence on developing students' financial literacy at MI NU Miftahul Ulum Kejapanan Pasuruan. The study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with Fiqh teachers and sixth-grade students, and documentation. The data analysis followed the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The results indicate that the implementation of the role-play method significantly enhances students' financial literacy across three dimensions: knowledge, attitudes, and skills. Students demonstrated a better understanding of Fiqh concepts, internalizing values such as honesty (sidq), justice (‘adl), and responsibility (amanah), while successfully practicing transaction procedures. In conclusion, the role-play method effectively transforms teacher-centered learning into an active, participatory, and meaningful experience. The implication of this research suggests that integrating experiential learning methods like role-play into Islamic education can bridge the gap between theoretical religious concepts and practical economic life, providing a foundation for students to face modern financial challenges based on Sharia principles.